Evaluasi Sistem Drainase Perkotaan Berdasarkan Curah Hujan Studi Kasus : Jalan Bambu Hingga Jalan Perjuanagn, Kota Medan, Sumatera Utara - Annisa Zahra Fakhira; Khalill Gibran Diqri; Wisnu Prayogo; Rizky Simanjuntak; Rumilla Harahap (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
Urban drainage systems play an important role in controlling stormwater runoff to prevent flooding and surface water ponding. This study aims to evaluate the condition of the drainage system on Jalan Bambu based on rainfall influence and the physical condition of the channels. The method used was direct field observation on six channel segments (Segments I–VI), including measurements of geometric parameters such as width, depth, and sediment height, as well as identification of existing channel conditions. The results show that most drainage channels experience a decline in function due to sediment deposits, organic and inorganic waste, and the growth of wild vegetation. The channel width ranges from 85–130 cm with depths of 52–224 cm, while sediment height reaches 5–14 cm. These conditions reduce flow capacity and increase the risk of flooding during high rainfall events. Some segments remain in relatively good condition, although waste accumulation still indicates insufficient maintenance. In conclusion, the drainage system on Jalan Bambu is not yet functioning optimally due to sediment and waste accumulation that obstructs flow. Therefore, channel normalization, routine maintenance, and increased public awareness of environmental cleanliness are required to improve drainage performance.